Space Positioning and Tracking Solutions for Military Applications (Advances in Military Technology, 2019)
This paper is discussing the current and new satellite transponders for global tracking and detecting of military assets and personnel at sea, on the ground and in the air for enhanced traffic control and management. These transponders are able to monitor all military mobile vehicles, to improve safety of movements and collision avoidance, especially for navy and air forces assets. By using Global Navigation Satellite System (GNSS) in integration with Inmarsat, Iridium and other satellite systems in one unit with antenna, it is possible to provide reliable positioning and tracking solutions for civilian or military mobiles and personnel. The existing and forthcoming space and ground segment for positioning and tracking solutions as a modern Satellite Asset Tracking (SAT) onboard mobiles and other relating systems are discussed and benefits of these new technologies and solution for improved positioning and tracking are explored.
Keywords: GNSS; GPS; GLONASS; MEO; SCS; SNS; SSS